REPRESENTASI GENDER DALAM FILM TELEVISI KISAH NYATA - Handayanti, Asih; Septadinusastra, Vina Alvinia; Rahayu, Asri Sri; Haryadi Mujianto; Neni Yulianita (Jurnal Spektrum Komunikasi, 2024)
The research was conducted on two Real Story FTV titles entitled "My Wife Is Like a Loaner Sucking My Money" and "My Feelings Are Being Played by My Husband". The research objective was to find out how gender is represented in Real Story FTV. This study uses a qualitative approach, with the method of critical discourse analysis model of Norman Fairclough. The analysis was divided into three stages, but the ones used in this study only reached the Text analysis stage (Micro level). The results of the study concluded that gender representation in the two FTV titles Real Stories is represented unequally, and causes gender bias. Many women are labeled as materialistic, money-crazed, usurpers, and men are labeled as someone who is unfaithful. The conclusion is that the media, through the FTV TV Show Real Stories, still represents gender unfairly, causing gender bias among the public to be difficult to eliminate.